Konsep Mediasi Berbasis Hadis Nabi dan Implementasinya dalam Sistem Peradilan Modern Indonesia - Muhammad Achyar Hamid; Abdul Rahman Sakka; St. Aisyah Kara (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
This study explores the application of mediation values contained in the Prophet Muhammad’s hadith within the framework of Indonesia’s modern judicial system. Using a normative-theological approach and a descriptive-analytical qualitative method, the research examines hadiths related to iṣlāḥ (reconciliation) alongside national regulations, particularly Supreme Court Regulation No. 1 of 2016, as the contextual foundation. The findings reveal that the principles of iṣlāḥ in the hadith emphasize justice (‘adl), compassion (raḥmah), sincerity (ikhlāṣ), and public welfare (maṣlaḥah) as the ethical pillars of mediation. These values parallel and complement the paradigm of restorative justice in contemporary law. However, mediation practices in Indonesian courts are often understood merely as administrative procedures, leaving the spiritual and transformative dimensions of the hadith underrepresented. This paper proposes an integrative model emphasizing the capacity building of mediators based on Islamic ethics, the formulation of a mediation code of conduct combining theological and technical aspects, and judicial policies that assess mediation outcomes not only quantitatively but also qualitatively, such as the restoration of relationships and the inner peace of disputing parties. Further recommendations include developing an “Islamic Mediation Ethics” curriculum in legal education institutions and conducting future research on the application of hadith-based mediation principles in criminal, family, and economic law. Thus, mediation grounded in the Prophetic tradition not only reduces the burden of the judiciary but also strengthens the law’s role as an instrument of moral cultivation and social welfare.